Pengaruh Sistem Keuangan Desa Dan Sistem Pengendalian Intern Terhadap Akuntabilitas Pengelolaan Dana Desa - Andriyawan E. Karim; Harun Blongkod; Siti Pratiwi Husain (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of the village financial system and internal control system on the accountability of managing village funds in the districts of Bilihu and Gorontalo. This research involved village heads, village secretaries, hamlet heads, BPD, youth leaders, and community leaders, totaling 113 respondents. Descriptive analysis, a structural equation model (SEM), and AMOS 24.0 were used in this study. This quantitative research combines primary data obtained through observation, interviews, questionnaires, and pictures. The results of the study found that the village financial system and the government's internal control system both had a positive and significant effect on the accountability of village financial management in villages throughout Biluhu District, Gorontalo Regency. Keywords : Village financial system, Internal Control System, Fund Management Accountability